The global geographies of mining and local expectations: the case study of a new coalmine project in Makhado Limpopo - Muzhambi, Desire Marandela (My University, 2021)
Globalization and spatial networks have changed the spatial planning of the world wherein global geographies of the mining, farming, and agriculture sectors have changed. Previous researches have shown that the mining industry in South Africa has attracted foreign companies that have connected South Africa to the rest of the world. The mining industry has positive and negative impacts, but the negative impacts are often localized. This study examines the globalized geographies of capital in the mining industry and the local expectations of change, it makes use of the new coal mine in Makhado as a case study. It considers the ways in which global mining interests and geographies land in place including how these come to be translated and mediated. It does this by exploring the way it lands in place in terms of promises, the expectations and consequences that are immediate and within a longer-term horizon. Local communities that are affected by mining continues to be cut off from access to the benefits of global economies. Through the network analysis, interviews, and mapping amongst other research methods, this research argues that mining has connected the world, but impacts are localized. Moreover, the local people access those networks through gatekeeping systems in their communities. It is because of the mining industry that the local is implicated in the global. We cannot understand a place like Makhado and how underdevelopment has affected the community without understanding how it is the community is situated into the broader networks. On the other hand, the majority of people are excited about the possible developments but are not aware of the environmental, health, social and cultural impacts that will be imposed on their community and surrounding communities by the mine. The research, therefore, shows that people are continuously being cut-off, and this is mainly because of past injustices of apartheid, and the traditional council legislation that enforces the gatekeeping system. Additionally, there is miscommunication between the mining company, the traditional council, and the local hosting community, which had led to contestations and misinformation around the mining project and mining industry, respectively.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2021